Cross-cultural analysis the science and art of comparing the world's modern societies and their cultures - Minkov, Michael (Los Angeles, [Calif.] ; London : SAGE, 2013)
This text critically examines all current, prevalent methods that have been developed in cross-cultural analysis, offering students and researchers the theoretical and practical advantages and potential pitfalls of each approach.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Cross-cultural studies -- Research